Indicadores de desempenho tático-técnicos no tie-break: estudo no voleibol de praia feminino de alto nível - Lima, Vanessa da Silva (2023)
Tie break is the third and decisive set in beach volleyball matches, where the first team to score 15 points with a two-point advantage over the opponent wins that set and the match. It is a critical moment of the game where the ability of the athletes to give their best is tested. Thus, the team's behavior at this time can determine its technical and tactical performance and the success of the team. Technical and tactical indicators are among the most studied in the analysis of the game in beach volleyball. However, match contexts such as set type, set period, and match period are still little studied. The aim of the study was to investigate the technical and tactical performance indicators in the tiebreak of elite women's beach volleyball. Game actions of all tie break sets (n = 31) played between balanced opposition teams in the FIVB Women’s Beach Volleyball World Championships (2019 and 2022) were observed by video analysis. TEBEVOL was used as an observation instrument. The variables analyzed were: technical and tactical indicators (attack, reception, set, attack, block, and dig) of the game phases (side-out, counter-attack (complexes II, III, IV)), tie-break result (win and loss), tie break type by victory margin (minimum: 2 points, medium: 3-4 points, maximum: >5 points), and tie break period (initial: 1 to 5 points, intermediate: 6 to 10, and final 11 at the end of tie break). Inferential analysis with practical significance indicated indicators of differences between tie break outcomes in general and based on the final point difference. Generalized models were used to influence the result and the period on indicators, the association of indicators in each period with the chances of winning, and the relationship between the indicators of performance in the final period in each outcome and the difference of end points. The results showed significant differences for winning teams in KII points, opponent errors in KIII attack, block, and attack efficacy. Most changes occurred for winning teams with more than 5 points in the final difference. The serve and KII block stood out in the middle scoring, while the side-out attack was more important in the smallest difference in the scoring. The intermediate and final periods of the tie break for the winning teams positively influenced the side-out attack. Teams with the best performance in the block (initial, intermediate, and final periods) and dig (initial period), counter-attack attack (final period), side-out attack (final period), as well as fewer serve errors (intermediate and final period), increase their chances of winning the tie break. It is concluded that most of the performance indicators studied were different for winners and losers depending on the difference in the final score and the period in the tie-break played.